Approach to Breast Lesions with Radiology-pathology Discrepancy: Discussion Based on 3 Cases Diagnosed with Malignancy After Surgery - Sümeyra Emine Bölük; Gülçin Ercan; Leman Damla Ercan (Caucasian Medical Journal)
Breast lesions are mainly classified as benign and malignant. When breast cancer is diagnosed, the patient is evaluated and a treatment plan is prepared. For benign lesions, follow-up or surgery may be performed. Imaging and biopsy results are essential when deciding on surgery. In particular, when there is a discrepancy between radiologic imaging and pathology results, excision may be useful for definitive diagnosis. We planned to present an approach to suspicious breast lesions with radiology pathology discordance through the presentation of three patients diagnosed with malignancy. Between February 2018 and March 2023, patients who underwent wire marking and excision for suspicious breast lesions were analyzed. Three patients diagnosed with malignancy after total excision were analyzed in detail. Of 33 patients, 2 (6.06%) patients had ductal carcinoma in situ and 1 (3.03%) patient had invasive tubular carcinoma. Preoperative and postoperative pathological findings were consistent with benign changes in all three cases. After total excision, a definitive diagnosis was made, and follow-up and treatment were planned. In cases of radiology-pathology discordance, total excision may be effective in detecting atypia, carcinoma in situ, or invasive carcinoma not detected on pathologic examination. Therefore, even if the biopsy result is not malignant, wire-guided total excision of radiologically suspicious lesions should be considered as a diagnosis and treatment method.